Empowering Scientific Attitudes in Biology Students through the SIRI Learning Model - Asham Bin Jamaluddin; Muhiddin Palennari; Faisal; Arsad Bahri; Andi Citra Pratiwi (Jurnal Penelitian Pendidikan IPA, 2024)
This study aimed to investigate the effect of SIRI learning model in empowering scientific attitudes in biology students. This experimental study was conducted with a nonequivalent pretest-posttest control group design and involved 95 biology students at Makassar State University, Indonesia. Data were collected using a scientific attitude questionnaire. The scientific attitude rubric was used to assess students' statements and the results were analyzed using ANCOVA at the 0.05 level of significance. The findings showed that there was an effect of SIRI learning model on scientific attitudes in biology students. The LSD test results also showed that the scientific attitude scores using the SIRI model were significantly different from the STAD learning model and the lecture model class. It is concluded that the SIRI learning model can improve scientific attitudes in biology students.